Developing student’s metacognitive ability in science through project-based learning with e-portfolio - Marheny Lukitasari; Rusdi Hasan; Akhmad Sukri; Jeffry Handhika (Institute of Advanced Engineering and Science, 2021)
The present study aimed to investigate the metacognitive ability of students using e-portfolio assessment in project-based learning classes. The projects were a set out a critical analysis based on the selected references (project 1) and set out of field activities based on the selected theme content (project 2). Student metacognitive ability consists of three phases, planning, implementation, and evaluation abilities that were assessed through e-portfolio assignments. There were 87 participants who divided into groups consisted of four to five students, conducted the projects, and submitted the progress of their projects in every decided step into online report assignments. The rubric of metacognition was used to acquire the quantitative score of skill that was separated into six levels category: not yet, at risk, not-really, developing, OK, and super. The result revealed that 44.83% of the students belong to the last three of those levels and the rest are otherwise. The lowest and highest metacognitive ability of the student is “not really” and “developing” respectively. Student metacognitive ability through conducting the project 2 activities is higher than project 1. The findings showed that project-based learning (PBL) enables to foster the student metacognitive ability that developed through e-portfolio-based documents that student conducted during fulfilling all projects assignments.The aim of present study was to investigate the metacognitive ability of student using e-portfolio assessment in the project-based learning classes. The projects were the set out a critical analysis based on the selected references (project 1) and the set out of field activities based on the selected theme content (project 2). Student metacognitive ability consists of three phases, planning, implementation and evaluation abilities that were assessed through e-portfolio assignments. Eighty-seven participants divided into groups consisted of four to five students, conducted the projects, and submitted the progress of their projects in every decided step into online report assignments. The rubric of metacognition was used to acquire the quantitative score of skill that was separated into six levels category; not yet, at risk, not really, developing, OK, and super. The result revealed that 44.83% of the students belong to the last three of those levels and the rest are otherwise. The lowest and highest metacognitive ability of student is